‘You’re Getting Two For One With Me’: Difficult New Sites Of Community Engagement Leadership Within Higher Education - Peacock, David; Campbell, Katy (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2023)
This article profiles the professional identities of two postsecondary staff leading the adaptation and adoption of the elective Carnegie Classification for Community Engagement in their institutions in Australia and Canada. It explores the tensions and frustrations, as well as opportunities, experienced by these “third space” or “community engagement professional” staff, who often struggle to find recognition of the value of their work within their institution. These staff portraits point to two sources of both personal and institutional misrecognition of community engagement professionals and the community engagement practice more generally: gender intersecting with race, and the relegation of community engagement to an external relations function that runs parallel to the core academic purposes of the institution.